CAPACITY BUILDING OF THE PPKS TASK FORCE AT SMAN 2 SEMARANG IN MITIGATING THE THREE MAJOR SINS IN EDUCATION BASED ON PANCASILA VALUES - Masrukhi; Wijayanti, Tutik; Pramono, Didi; Irawan , Hendri (Progress In Social Development, 2025)
Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), has shown a strong commitment to eliminating the three major sins in education sexual violence, bullying, and intolerance as stipulated in Regulation No. 46 of 2023. This policy has inspired various initiatives within educational institutions, one of which is the establishment of the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) at SMAN 2 Semarang. This task force was formed in response to the increasing number of social deviance cases in schools, with data indicating 115 cases of sexual violence, 61 cases of bullying, and 24 cases of intolerance. This study aims to describe and analyze the capacity building of the Satgas PPKS in carrying out its role as a mitigation agent based on Pancasila values. This research uses a qualitative approach with a case study method through participatory observation, in-depth interviews, and training sessions conducted by a community service team from Universitas Negeri Semarang (UNNES). The findings show that Pancasila values serve as a crucial foundation for shaping students’ character to uphold tolerance, justice, and humanity. In this context, UNNES, as a Teacher Training Institution (LPTK), plays an active role in guiding and strengthening the capacity of the Satgas PPKS. Through this initiative, a strategic collaboration is built to create a safe, inclusive, and Pancasila-oriented school ecosystem